The Role of Cloud Computing in Development of Management Information Systems in The Telecommunication Companies - Abeer Kadum Olleiwi (Universitas Komputer Indonesia, 2026)
This study aimed to investigate the contribution of cloud computing, in its four dimensions (Software as a Service, Platform as a Service, Infrastructure as a Service, and Hardware as a Service, HaaS), to the development and growth of Management Information Systems (MIS) within the Iraqi telecommunications sector, specifically in the companies Asiacell and Zain Iraq. To achieve this objective, the study adopted a descriptive-analytical approach, developing a questionnaire as the primary data collection tool. Data was collected from a purposive sample of 87 administrative and technical staff members. The data was processed and hypotheses tested using the Statistical Package for the Social Sciences (SPSS). The field results showed a high level of strategic adoption of cloud computing technologies, with an overall mean score of 3.737. The Software as a Service (SaaS) model emerged as the most widely applied and consistent dimension, with a mean score of 3.837. The study also revealed a strong positive correlation (0.850) between cloud adoption and information systems development. Regression analysis demonstrated that cloud computing explains 72.2% of the variance in the efficiency and effectiveness of management systems. The study concludes that digital transformation towards cloud environments is no longer a secondary option but a necessity to enhance data processing speed and support decision-making. It recommends increased investment in cloud infrastructure, training of personnel on modern technologies, and the establishment of robust cybersecurity frameworks to ensure service sustainability and data privacy protection.